The Fate of Bacteria in Human Digestive Fluids: A New Perspective Into the Pathogenesis of Vibrio parahaemolyticus - Wang, Siqi; Zhang, Zhaohuan; Malakar, Pradeep K.; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2019)
Vibrio parahaemolyticus causes the most seafood attributed gastroenteritis outbreaks worldwide and studies on pathogenesis during passage through the human digestive fluids are limited. An in vitro continuous model system mimicking passage through saliva, gastric and intestinal fluid was used to study the survival, morphology and virulence-related gene expression of 60 pathogenic and non-pathogenic V. parahaemolyticus strains. The changes to these 3 characteristics for the 60 V. parahaemolyticus strains were minimal on passage through the saliva fluids. No V. parahaemolyticus strains survived passage through gastric fluid with low pH values (2.0, 3.0) and the cells, examined microscopically, were severely damaged. However, when the pH of gastric fluid increased to 4.0, the bacterial survival rate was 54.70±1.11% and the survival rate of pathogenic strains was higher when compared to non-pathogenic strains. Even though the bactericidal effect of intestinal fluid was lower than gastric fluid, virulence-related gene expression was enhanced in the intestinal fluid. Seafood matrices can significantly raise the pH level of gastric fluid and thus aids the survival of V. parahaemolyticus through passage from human gastric acid and progression of pathogenesis in the intestinal fluid. We confirmed these phenomena in the in-vitro continuous digestion model.